The Efforts to Improve Marketing Performance in Small and Medium Industries of Tofu - Ma'arif, Aslama Odilak; Maftukhah, Ida (Management Analysis Journal, 2020)
Small and Medium Industries have become the largest industry in Indonesia that has an important role in the Indonesian economy due to its ability to encourage economic growth and create new sources of entrepreneurship. Small and Medium Industries are expected to be more creative and prepared in marketing strategies to deal with an increasingly complex business environment. This study aims to examine the effect of marketing knowledge competence and entrepreneurial orientation on marketing performance through marketing capabilities. The population in this study was the Small and Medium Industries of Tofu in Magelang City. The number of samples used was 94 respondents. The sampling technique uses saturated samples. The data were analyzed using the method of descriptive analysis, regression analysis, and path analysis using IBM SPSS version 22. The results of the study show that marketing knowledge competency and entrepreneurial orientation have a positive and significant effect on marketing performance. Marketing capability could mediate the influence of marketing knowledge competencies and entrepreneurial orientation on marketing performance. The advice given is that the Small and Medium Industries of Tofu practitioners should innovate more in tofu products, conduct promotions, provide the best service to customers, and be able to maintain the quality of tofu. The next researcher is expected to add references related to marketing knowledge competence and expand the scope of the object.